Landing Performance Study for Four Wheels Twin Tandem Landing Gear Based on Drop Test - Wei Fang; Lingang Zhu; Youshan Wang (Aerospace, 2022)
The drop tests of a twin tandem landing gear with different filling parameters are carried out in two different landing attitudes (level and tail-down). The overload coefficient and power absorption efficiency are obtained. Curves of dynamic oscillation and pressure change for the pitch damper are obtained. The results show that twin tandem landing gear has a good ability to absorb the work of landing impact. Under landing weight, the vertical overload coefficients during level landing and tail-down landing are 1.14 and 1.07, respectively, when the corresponding efficiencies of its buffer system are 80.9% and 83.3%. During tail-down landing, the work absorbed by the pitch damper accounts for only 14.9% of the maximum pitching kinetic energy of the trolley. When the orifice diameter of the pitch damper keeps the same, its peak axial load does not change significantly with the change of its initial pressure. When the initial pressure of the pitch damper keeps the same, the decrease of its orifice diameter is beneficial to the vibration attenuation of the trolley. The smaller recoil channel may lead to a significant increase in the peak pressure of the pitch damper, which should be a consideration in its design.